STUDY ON SCRAPER CONVEY OR CHAIN TENSION TESTING SYSTEM - QI XiuFei; ZHANG Pei; HAO ZhiYong; YAN Chuang (Jixie qiangdu)
In order to study the mechanical properties of scraper conveyor chain under complicated conditions,the scraper conveyor chain tension changes during the operation of on-line monitoring was realized,The wireless transceiver module and storage testing data signal,export to stay after the test data and analysis were carried out. Experimental results showed that the same round link chain of two straight tension appeared the obvious unequal phenomenon; Coal winning machine cutting coal,increased near the coal mining is bigger than the lateral side chain tension goaf side chain tension. Image shows that whenever the chain after a sprocket will produce a Zhang Lijie leap mutation,half the no-load operation cycle time interval of 51 s,scraper conveyor motion resistance of 16 kN no-load current end,chain tension value is 896 k N. The results of the study provides theory basis for design and optimization of the chain.